Surface Activity and Efficiency of Cat-Anionic Surfactant Mixtures - La Mesa, Camillo; Risuleo, Gianfranco (Frontiers in Chemistry, 2021)
The surface activity of surfactant mixtures was critically analyzed. Cat-anionic systems, in which two ionic species are mixed in non stoichiometric ratios, are considered. With respect to the solution behavior, where a substantial decrease of cmc is met compared to the pure oppositely charged ionic components, a moderate effect on the surface activity, γ, occurs. The decrease of surface tension is not significant if compared to the pure species, and no dependence on the mole fraction anionic/cationic is ever met. The interaction parameter for surfaces, βsurf (calculated by the regular solution theory), is more negative than for micelle formation, βmic. The underlying rationale finds origin in the sizes of polar head groups.